Doctor Diego Meneses Almeida - Morales Navarro, Denia (Revista Cubana de Estomatología, 2013)
On Tuesday, August 28, 2012, we received the sad news of the death in his home of Dr. Diego Meneses Almeida, specialist of II Degree in Maxillofacial Surgery, which until the last moments of his life worked in the University Hospital "General Calixto García". At the time of his death he held the main teaching category of assistant professor and since 2000 he had been appointed as consulting professor. Professor Diego Meneses began his studies of Dentistry in 1953, which concluded after the revolutionary triumph. From these early years he contributed to the development of teaching in the career of Stomatology, an activity that would develop flawlessly throughout his life. He worked in several centers, but gave himself completely to the creation and development of the Maxillofacial Surgery service of the University Hospital "General Calixto García", institution where he worked for 44 years and dedicated himself to the care work, mainly aimed at the attention to maxillofacial trauma . As a teacher linked to the Faculty of Stomatology of the University of Medical Sciences of Havana, he contributed to the formation of dozens of generations of stomatologists and maxillofacial surgeons from Cuba and the world. Throughout his life he received multiple distinctions and recognitions for his teaching and internationalist work. He was part of the Board of Directors of the Cuban Society of Maxillofacial Surgery and the National Specialty Group. His impeccable professional and personal behavior earned him the respect and consideration of those who had the privilege of surrounding him and having his support, aspects that caused a deep pain in his physical disappearance. His memory will be imperishable insofar as the actions of the new professionals, which he helped to form, are consistent with his example in the affection, seriousness and love he instilled in everyone.